Validation of a questionnaire on research-based learning with engineering students - Fabián Cobos Alvarado; Mónica Peñaherrera León; Ana María Ortiz Colon (OmniaScience, 2016)
Universities in Latin American countries are undergoing major changes in its institutional and academic settings. One strategy for continuous improvement of teaching and learning process is the incorporation of methods and teaching aids seeking to develop scientific research skills in students from their undergraduate studies. The aim of this study is the validation of a questionnaire to measure research skills with engineering students. Questionnaire validation was performed by: literature review, semantic and content validation by experts from three Latin American universities, finishing with a factorial and reliability validation. The instrument was applied to 150 students (75,3% men and 24,7% women) that were enrolled in the basic level of engineering. The validated questionnaire has 20 items. The correlations between factors of the instrument, show relationship and dependence between them, indicating the validity of the questionnaire. The reliability of the instrument was calculated using Cronbach's alpha coefficient, which reached a value of .91 in the total scale. The statistical results to validate the questionnaire have been significant, allowing us to propose this experience as a starting point to implement further studies about the development of research skills in university's students from other areas of knowledge.